Paper 24: The Power of Information: Influence of Interim Function Assessments on Patient Outcomes at the time of Return to Sport Progression Following Anterior Cruciate Ligament Reconstruction. Issue 7 (30th July 2022) - Bruce, Amelia; Diduch, David; Miller, Mark; Brockmeier, Stephen; Gwathmey, F. Winston; Werner, Brian; Hart, Joseph; Bodkin, Stephan
Objectives: The administration of return to sport assessments have become common in patients following Anterior Cruciate Ligament Reconstruction (ACLR). However, they are often administered after the time of clinical supervision which may leave patients without access to clinical personnel to appropriately address the functional deficits identified. It is currently unknown if patient outcomes would benefit from interim functional assessments while under clinical supervision. The purpose of this study is to compare patient outcomes at the time of return to sport (RTS) progression between those with a prior interim assessment and those without. We hypothesize that patients with prior interim assessments will demonstrate stronger and more symmetric quadriceps strength, greater hopping performance, and higher subjective function. Methods: Patients following ACLR were retrospectively identified through an ongoing RTS assessment program where patients were referred from a sports medicine subspecialist orthopedic clinic to complete a battery of functional assessments This program assessed knee extensor and flexor strength (Nm/kg) and symmetry (%) and patient reported outcomes. Patients were stratified into "Single Test": first assessment between 6- and 9-months post-ACLR and "Repeat Test": prior assessment performed at least 2-months before RTS assessment between 6- and 9-months post-ACLR (Figure 1). Patients were matched based on time post-surgery, age, pre-injury activity level, and graft type. Results: A total of 392 patients were included (Single Test n=303, Repeat Test n=89.) Once matched, 169 patients (21.1±7.0 years, 7.3±.9 mo. post-ACLR) were analyzed (n=69 per group, Figure 2.) Controlling for age, activity level, graft type, and time of the assessment, Repeat Test patients demonstrated higher measures of subjective function ( P =.028) and greater knee flexion symmetry ( P =.006) compared to Single Test patients. There were no differences in quadriceps strength ( P =.82) and symmetry ( P =.18) between groups. Conclusions: Patients that received interim functional assessments reported better subjective function and higher hamstring symmetry at the time of return to sport progression compared to patients that completed their first and only assessment at this time-point. Interim referral for functional assessments may identify limitations which medical provides can address prior to the time of RT progression.